A Functional Chemiluminescent Probe for in Vivo Imaging of Natural Killer Cell Activity Against Tumours. (2nd February 2021) - Scott, Jamie I.; Gutkin, Sara; Green, Ori; Thompson, Emily J.; Kitamura, Takanori; Shabat, Doron; Vendrell, Marc
Abstract: Natural killer (NK) cells are immune cells that can kill certain types of cancer cells. Adoptive transfer of NK cells represents a promising immunotherapy for malignant tumours; however, there is a lack of methods to validate anti‐tumour activity of NK cells in vivo. Herein, we report a new chemiluminescent probe to image in situ the granzyme B‐mediated killing activity of NK cells against cancer cells. We have optimised a granzyme B‐specific construct using an activatable phenoxydioxetane reporter so that enzymatic cleavage of the probe results in bright chemiluminescence. The probe shows high selectivity for active granzyme B over other proteases and higher signal‐to‐noise ratios than commercial fluorophores. Finally, we demonstrate that the probe can detect NK cell activity in mouse models, being the first chemiluminescent probe for in vivo imaging of NK cell activity in live tumours. Abstract : In vivo detection of natural killer (NK) cell activity against tumours was achieved with an activatable chemiluminescent probe containing a granzyme B‐reactive peptide substrate linked to a phenoxydioxetane scaffold through a p ‐aminobenzyl alcohol linker. The rapid and specific chemiluminescence response of the probe was used to detect NK cell activity against breast cancer cells in living mice.